2016
DOI: 10.1038/srep30709
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of long non-coding RNA transcriptome in high-energy diet induced nonalcoholic steatohepatitis minipigs

Abstract: Today, obesity and nonalcoholic steatohepatitis are a worldwide epidemic, although how these syndromes are regulated with respect to lncRNAs remains largely unknown. Our previous studies have revealed important pathological features and molecular characteristics of nonalcoholic steatohepatitis in the minipig model, and in this study, we analyze the features of lncRNAs and their potential target genes. Minipig samples only from liver were analyzed using next-generation deep sequencing. In total, we obtained 585… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…In contrast to mRNAs, lncRNAs are generally expressed in low amounts, typically an order of magnitude lower than mRNA expression levels 2,5,[8][9][10] . Furthermore, several studies demonstrated that lncRNA expression levels are very noisy, which is a characteristic shared with low count data from massively parallel RNA sequencing [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to mRNAs, lncRNAs are generally expressed in low amounts, typically an order of magnitude lower than mRNA expression levels 2,5,[8][9][10] . Furthermore, several studies demonstrated that lncRNA expression levels are very noisy, which is a characteristic shared with low count data from massively parallel RNA sequencing [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, fatty acid β-oxidation in the mitochondria plays an important role in energy homoeostasis, and mitochondrial dysfunction results in a reduction of fatty acid β-oxidation, which is a critical feature of NAFLD. 11) NASH is characterized by intracellular triglyceride (TG) accumulation, liver fat deposition, inflammatory cell infiltration, ballooning of hepatocytes in the liver, and different degrees of fibrosis, 12,13) which result from an imbalance of increased lipids via circulating lipid uptake, de novo lipogenesis, or decreased lipid disposal primarily by FFA oxidation, and it is considered the first hit in the pathogenesis of NAFLD. The plasma FFA composition has been used to provide insight into cellular metabolic pathways.…”
mentioning
confidence: 99%
“…Previous studies have reported that IUGR mammals have increased hepatic gluconeogenic capacity, reduced hepatic lipolysis, and reduced fatty acid oxidation [4,42]. In a rat model, intravenous glucose tolerance test (i.v.GTT) indicates that IUGR will impairs its capacity of glucose tolerance [43]. Previous studies have shown that IUGR impairs hepatic mitochondrial oxidative phosphorylation and influences hepatic energy homeostasis [44].…”
Section: Discussionmentioning
confidence: 99%